Mosquitos antropofílicos de atividade matutina em Mata Atlântica, Florianópolis, SC Mosquitoes with morning biting activity in the Atlantic forest, Brazil (Diptera, Culicidae) - Uéslei Paterno; Carlos Brisola Marcondes (Universidade de São Paulo, 2004)
Como os trabalhos sobre Culicidae em Santa Catarina foram restritos a anofelíneos e a Culex quinquefasciatus, pela ocorrência, no passado, de malária e de filariose, a fauna de mosquitos em áreas de mata é pouco conhecida. Assim, foi realizado um levantamento dos culicídeos que atacam o homem pela manhã em trilha situada numa unidade de conservação da Mata Atlântica na Ilha de Santa Catarina, freqüentada por estudantes e turistas. Foram coletados 358 exemplares de 22 espécies, das quais 14 são relatadas pela primeira vez no Estado. Runchomyia reversa e Ochlerotatus scapularis foram as espécies predominantes, com grande diversidade de espécies de Wyeomyia (Phoniomyia). Previous studies on Culicidae in the state of Santa Catarina, Brazil, were limited to Anophelinae and Culex quinquefasciatus due to the past occurrence of malaria and filariasis but the mosquito fauna in forested areas is still almost unknown. It was carried out a survey of mosquitoes with morning biting activity in a tourist trekking trail of an Atlantic forest reserve area in the island of Santa Catarina. There were collected 358 specimens of 22 species, 14 of them reported for the first time in the state. Runchomyia reversa and Ochlerotatus scapularis were the predominant species. There was a great diversity of Wyeomyia (Phoniomyia) species.